Evaluation of Heavy Metal Removal from Wastewater Using Iranain Modified Natural Clinoptilolite - Masrournia, M. (Asian Journal of Chemistry, 2013)
In this study, the absorption properties of the natural zeolite (from east of Iran) with respect to some heavy metal cations in water solution were investigated. Clinoptilolite, a natural zeolite, was used for the removal of Cu2+, Co2+, Ni2+ and Cd2+ ions from water samples. The batch method has been employed. Satisfactory result was obtained by using pretreatment condition and regeneration. The percentage adsorption and distribution coefficient were determined for the absorption cations as a function of sorbate concentration. In the ion exchange evaluation, two sorption isotherms, Langmuir and Freundlich have been studied. Cation exchange selectivity can be given as Cd2+ > Cu2+ > Co2+ >Ni2+. These results show that these natural zeolites can be used efficiently for removal of heavy metal species from wastewater.